Gramíneas forrageiras em consórcio com soja, visando os sistemas integrados de produção agropecuária - Machado, Luís Armando Zago (2016)
The intercropping is an agricultural practice that results in more utilization efficiency of solar radiation and provides productivity increase of involved crops. This study aimed to evaluate the establishment of seven perennial forages in intercropped with soybean, targeting integrated crop-livestock systems. The objective of this study was to evaluate soybean and forages production in intercropping as well as the bromatologic composition and grasses susceptibility to glyphosate herbicide, for integrated crop livestock system. A randomized blocks design in seven replicates was used. It were evaluated cultivation methods (intercropping): 1) sole soybean crop; 2) Soybean + Megathyrsus maximus cv. Aruana; 3) Soybean + M. maximus cv. BRS Tamani; 4) Soybean + Urochloa brizantha cv. Xaraés; 4) Soybean + U. brizantha cv. BRS Piatã; 6) Soybean + U. brizantha cv. BRS Paiaguás; 7) Soybean + U. decumbens; and 8) Soybean + U. ruziziensis. The forages were planted between 14 and 21 days after soybean emergence, in the periods 2011/2012 and 2012/2013 respectively. The forages were sown in the inter-rows between 14 and 21 days after soybean emergence, in the periods 2011/2012 and 2012/2013 respectively. In the forage sowing were controlled the weeds and herbicide was no more applied until the end of the soybean cycle. Grain yield components of soybean and variables related to annual crops, forages and weeds plants were evaluated. Subsequently, the forages were evaluated under successive cuts during the dry season. In the first year, all forages were evaluated on the same date, on three occasions. In the second year, each experimental unit was evaluated undercut when achieved 95% of light interception. Leaf blade and stem were determined, and bromatologic analysis was carried in the first fraction. At the beginning of rainy season it was evaluated the forages susceptibility to glyphosate herbicide in the doses 0.72 and 1.44 kg a. e. ha-1. The control percentage was determined in one grading scale of zero (all live tillers) to 100 (all dead tillers) at 7, 14, 21 and 28 days after herbicide application. It was not observed difference in grain yield between the intercrops and sole soybean, except for soybeans + U. ruziziensis and soybean + BRS Paiaguás, which were less productive than the control, in the period 2012/2013. The soybean harvested intercropped with U. ruziziensis showed a higher impurities and moisture percentage of the grains in the two crop years. The BRS Tamani and Xaraés grasses presented more leaf blades and higher leaf/stem ratio, an important feature in grazing condition. U. ruziziensis, one of the main forage used in integrated systems, presented the lowest production of leaf blades. This species and the BRS Paiaguás and Aruana grasses were the most susceptible forages to glyphosate herbicide, important feature for crop succession under no-tillage. In conclusion, it is possible to establish perennial forages intercropped with soybeans without changing the grain yield of the annual crop. Forages such Tamani grass are appropriate to establish in intercrop with soybean considering its morphological characteristic and the low potential competition. Soybean and perennial forages in intercrop contributes to suppression of weed growth. Between the forages evaluated the BRS Tamani grass is the one with the greatest potential for use in integrated crop-livestock systems, when established with soybean, considering their productivity and chemical composition of the produced leaf blade and its morphological characteristics, small size and high leaf:stem ration, which can facilitate its manager. The BRS Paiaguás grass can replace U. ruziziensis in integrated crop-livestock systems with advantages to be more productive. Forages susceptibility to glyphosate herbicide varies among species and cultivars. The genotypes U. ruziziensis, BRS Paiaguás and Aruana are desiccated with reduced herbicide dose with short desiccation time and can contribute to the forage diversification used in integrated crop-livestock systems.